2021
DOI: 10.1155/2021/9367778
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective View of Cotton Leaf Image Classification Using Machine Learning Algorithms Using WEKA

Abstract: Cotton is one of the major crops in India, where 23% of cotton gets exported to other countries. The cotton yield depends on crop growth, and it gets affected by diseases. In this paper, cotton disease classification is performed using different machine learning algorithms. For this research, the cotton leaf image database was used to segment the images from the natural background using modified factorization-based active contour method. First, the color and texture features are extracted from segmented images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…This paper also included basic ideas about transfer learning with some research questions Abade et al (2021). Patil and Burkpalli. (2021), this paper presents image classification for cotton leaves using machine learning algorithms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper also included basic ideas about transfer learning with some research questions Abade et al (2021). Patil and Burkpalli. (2021), this paper presents image classification for cotton leaves using machine learning algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper, color features show the classification of healthy and diseased, cotton leaf images with an accuracy of nearly about 96.69% which is more than as com-pared to another classifier. Images from real fields and a database of 3000 images with 2 groups of healthy and diseases were used to classify cotton leaf diseases Patil and Burkpalli (2021). Raghavendra et al (2021a), this paper discussed multiple disease classifications and detection for different plant leaves using a support vector machine.…”
Section: Related Workmentioning
confidence: 99%
“…A probabilistic learning model based on the Bayes theorem, NB is one of the machine learning techniques used to predict the phenomenon of classifying several different classes [22], [25][26][27]. Equation for NB classifier shown in Eq.…”
Section: Naï Ve Bayes (Nb)mentioning
confidence: 99%
“…The experiments were carried out using SVM, multilayer perceptron, Random Forest, Naïve Bayes, KNN and AdaBoost. The work concluded that only colour features were sufficient to improve the accuracy of classification [19].…”
Section: Related Workmentioning
confidence: 99%